The Multifunctional Content of the Human Right to the Environment - Aghenitei, Mihaela (Journal of Danubian Studies and Research, 2023)
If the protection of the environment inevitably entails the attainment of fundamental freedoms, such as, for example, the right to property or the restriction of certain easements or the restriction of the right to move in certain protected areas, it ends up, as we have shown, to broaden other concerns. The right to the environment was initially closely linked to the right to health and the right to life; this later translated into the assertion of a right to better living and working conditions such as occupational health and safety and the development of the right to rest and recreation. But environmental law is the bearer of fundamental rights, such as the right to information and participation, decision-making, the right to association, and, thus, the strengthening of the social and collective function of existing rights. Law is the mass of duties both for the state and public authorities and for the individual. Environmental protection may be the reason for the increased participation of citizens in public life and the democratization of all procedures.